Monthly vitamin D supplementation, pain, and pattern of analgesic prescription: secondary analysis from the randomized, double-blind, placebo-controlled Vitamin D Assessment study. Issue 6 (June 2018) - Wu, Zhenqiang; Camargo, Carlos A.; Malihi, Zarintaj; Bartley, Jim; Waayer, Debbie; Lawes, Carlene M.M.; Toop, Les; Khaw, Kay-Tee; Scragg, Robert
Abstract : Abstract: Observational studies suggest that vitamin D deficiency is associated with higher risk of pain. However, evidence on the effect of vitamin D supplementation on pain is limited and contradictory. The aim of this study was to compare the effect of monthly high-dose vitamin D supplementation on a pain impact questionnaire (PIQ-6) score and prescription of analgesics in the general population. We performed a randomized, double-blind, placebo-controlled trial of 5108 community-dwelling participants, aged 50 to 84 years, who were randomly assigned to receive monthly 100, 000-IU capsules of vitamin D3 (n = 2558) or placebo (n = 2550) for a median of 3.3 years. The PIQ-6 was administered at baseline, year 1, and final follow-up. Analgesic prescription data were collected from Ministry of Health. There was no difference in mean PIQ-6 score at the end of follow-up (adjusted mean difference: 0.06; P = 0.82) between the vitamin D (n = 2041) and placebo (n = 2014) participants. The proportion of participants dispensed one or more opioids was similar in the vitamin D group (n = 559, 21.9%) compared with placebo (n = 593, 23.3%); the relative risk (RR) adjusted for age, sex, and ethnicity was 0.94 ( P = 0.24). Similar results were observed for dispensing of nonsteroidal anti-inflammatory drugs (RR = 0.94; P = 0.24) and other nonopioids (RR = 0.98; P = 0.34). Focusing on vitamin D deficient participants (<50 nmol/L, 24.9%), there was a lower risk of dispensing nonsteroidal anti-inflammatory drugs in the vitamin D group compared with placebo (RR = 0.87; P = 0.009); all other subgroup analyses were not significant. Long-term monthly high-dose vitamin D supplementation did not improve mean PIQ-6 score or reduce analgesic dispensing in the general population. Abstract : Supplemental Digital Content is Available in the Text.Long-term monthly high-dose vitamin D supplementation did not improve mean questionnaire pain score or reduce analgesic dispensing in the general population.